Paving the Way to the Gig Economy: A Bibliometric Analysis of Workers’ Decade-Long Involvement - Basnet, Prashiddha; Devkota, Niranjan; Chapagain, Ram Krishna; Mahapatra, Sushanta Kumar (Economic Journal of Nepal, 2024)
The gig economy, which comprises flexible, temporary, freelance jobs connecting workers with clients through online platforms, has garnered significant attention as a growing segment of the economy. The objective of this study is to understand the conceptual framework related to workers’ participation in the gig economy. To that end, we utilized the databases of Scopus, employing the bibliometric software VOSviewer. The dataset spans the last 10 years, from 2014 to December, 2023. Through our search, we initially identified 1429 articles, among which 1192 papers are from economics, econometrics, and business, and 856 papers are articles and review papers. Subsequently, we narrowed the selection to 821 articles written in English. The research is divided into two main parts: performance analysis and science mapping. Performance analysis focuses on developing visual representations of data, such as co-authorship, citation networks, and collaboration networks among authors, institutions, and journals. On the other hand, science mapping focuses on co-citation networks, co-occurrence networks, cluster analysis of the keywords, and thematic mapping. Over the past decade, there has been a significant increase in publications about the gig economy, reflecting the growing presence of gig workers. Policymakers must now prioritize integrating gig workers’ perspectives into policy development to ensure their unique needs are met effectively. The study represents one of the most comprehensive and meticulous bibliometric analyses of workers’ participation in the gig economy to date.